Strain-induced cesium bismuth bromide perovskite/bismuth oxide bromide composite with enhanced optical properties - Low, Yiin Jian; Ying Chyi, Josephine Liew; Talib, Zainal Abidin; Lim, Hong Ngee; Ahmad Kamarudin, Mazliana; Lim, Kean Pah; Lee, Han Kee; Mohd Noor, Ikhwan Syafiq; Salisu, Bashir (Elsevier, 2022)
Perovskite halides are well suited for optoelectronic applications because of their excellent optical properties. Among them, cesium bismuth bromide (Cs3Bi2Br9) has emerged as a promising lead-free optical material to replace lead-based perovskite halides. This can be achieved by introducing a hydrated perovskite passivation layer, BiOBr. However, previous work was solely limited to bismuth oxide bromide (BiOBr) passivation on the Cs3Bi2Br9 surface layer and did not address composite synthesis from two different phases. Herein, we report the discovery and characterization of Cs3Bi2Br9/BiOBr composite via a pre-precipitation method using isopropanol (IPA) and hydrous ethanol (EtOH). Williamson-Hall plot analysis of the X-ray diffraction (XRD) results showed the successful formation of a Cs3Bi2Br9/BiOBr composite with an induced-strain effect when EtOH was introduced. The ultraviolet–visible (UV–Vis) and photoluminescence (PL) spectra showed that the absorption and emission peaks of Cs3Bi2Br9 were located at 340 nm and 410 nm, respectively. A redshift in the absorption onset and energy bandgap generates a 190% increase in PL emission for the EtOH-synthesized perovskite sample. The enhancement is correlated to the induced effect in the Cs3Bi2Br9 phase, where BiOBr could act as an agent to improve the optical properties of Cs3Bi2Br9 by inducing strains other than the surface passivation layer.